2017
DOI: 10.1007/s12046-017-0734-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational model on pulsatile flow of blood through a tapered arterial stenosis with radially variable viscosity and magnetic field

Abstract: An unsteady two-fluid model of blood flow through a tapered arterial stenosis with variable viscosity in the presence of variable magnetic field has been analysed in the present paper. In this article, blood in the core region is assumed to obey the law of Jeffrey fluid and plasma in the peripheral layer is assumed to be Newtonian. The values for velocity, wall shear stress, flow rate and flow resistance are numerically computed by employing finite-difference method in solving the governing equations. A compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…D B is Brownian diffusion coefficient and D T is thermophoretic diffusion coefficient. The governing equations (7)- (11) in component form are as follows:…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…D B is Brownian diffusion coefficient and D T is thermophoretic diffusion coefficient. The governing equations (7)- (11) in component form are as follows:…”
Section: Governing Equationsmentioning
confidence: 99%
“…Reddy et al [9] modelled the blood as a couple stress fluid and concluded that it is a couple stress fluid having high impedance as compared with the classical Newtonian fluid. Some authors [10,11] theoretically studied the blood rheology on different kinds of obstructions like cerebral aneurysm and coronary artery disease (e.g., stenotic), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the blood rheology exerts a prominent role in the performance of the coil which is aimed at reducing fluid loading of the blood vessel and delaying subsequent wall deformation. Priyadharshini and Ponalagusamy [12] used a finite difference computational method to simulate time-dependent magneto-hemodynamics in a tapered arterial stenosis with variable viscosity, considering blood in the core region as viscoelastic Jeffrey fluid and plasma in the peripheral layer as Newtonian. They confirmed that the results with blood rheology included better correlate with experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of their experiments, it is more appropriate to represent the blood flow through narrow arteries by a two-layered model instead of the one-layered model. Shukla et al [17], Chaturani and Ponnalagarsamy [18], and Priyadharshini and Ponalagusamy [19] have discussed two-layered models in which the peripheral layer is *For correspondence a Newtonian fluid, and the core region is a non-Newtonian fluid (blood). Nallapu and Radhakrishnamacharya [20] have dealt with the problem of two-layered model of blood flow in small diameter tubes, where the core region consists of a Jeffrey fluid with constant viscosity and Newtonian fluid in the peripheral zone of plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Ponalagusamy and Tamil Selvi [23] analysed the two-fluid model of blood flow in stenotic arteries in which the fluid in both core and plasma layer is considered to obey the law of Newtonian fluid and considering the core viscosity of blood as a radial coordinate dependent. Priyadharshini and Ponalagusamy [19] examined a two-layered model of blood flow in an unsteady state where blood in the central core region is assumed to be a non-Newtonian (Jeffrey) fluid and a Newtonian fluid in the peripheral plasma layer by taking core viscosity as variable and applying a radially variable external magnetic field. Ponalagusamy [24] developed a two-layered model concerning measurable flow variables for flow of blood in a stenosed artery and derived formulas for computing axially variable plasma layer thickness, variable core fluid viscosity and axially variable slip velocity.…”
Section: Introductionmentioning
confidence: 99%